Role-playing For Internalizing Pancasila Values In PKn Learning: A Systematic Literature Review - Naimah Hidayati; Winarno Winarno; Fadhil Adi (Jurnal Ilmiah Sekolah Dasar, 2024)
Pancasila, as the foundational philosophy of the Indonesian state, plays a crucial role in shaping students' character and moral values. This study aims to analyze trends and evaluate the effectiveness of the role-playing method as a teaching strategy to internalize Pancasila values in civic education (PKn). A systematic literature review approach was employed by identifying 20 peer-reviewed articles published between 2014 and 2024 using the Publish or Perish (PoP) search engine, which accesses databases such as Scopus and Google Scholar. Thematic analysis was used to explore the relationships between concepts identified across the selected studies. The findings indicate a significant increase in the use of role-playing methods, with the highest publication trend occurring in 2024. Role-playing has been proven effective in fostering students’ understanding of Pancasila values through direct experience, reflection, and contextual simulation. Furthermore, this method contributes to the development of social and character-related skills, such as empathy, cooperation, and tolerance. The study concludes that role-playing holds considerable potential for broader implementation in civic education, particularly as a tool for strengthening character education grounded in Pancasila values.